Beyond Words: Merging Lexical and Contextual Models for Vocabulary Development through Idiom Learning - ARAB, Ouided (Journal of Human Sciences, 2025)
The mastery of idiomatic expressions is an important criterion determining EFL learners’ overall proficiency in English. Henceforth, the current study aims to investigate the possibility of enhancing students’ mastery of idiomatic expressions via a lexical-contextual model to extend EFL learners’ vocabulary repertoire. It takes the case of first-year students at the Department of Arts and English Language, Frères Mentouri Constantine 1 University.Two main research tools were adopted to achieve the aforementioned aim: an experiment and a delayed test.The pre and post-test findings revealed improved students’ mastery of idiomatic expressions. Furthermore, the delayed test results were in favour of the participants’ retention of their level in the post-test regarding vocabulary abilities by revealing the proper use of idioms in a variety of contexts in their written productions.